Developing the Curriculum - Oliva, Peter F. (Scott, Foresman/Little, 1988)
Curriculum and instruction defined.- Principles of curriculum development.- Curriculum planning: a multilevel, multisector process.- Curriculum planning: The human dimension.- Models for curriculum development.- Philosophy and Aims of Education.- Needs assessment.- Curriculum goals and objectives.- Organizing and implementing the curriculum.- Instructional goals and objectives.- Selecting and implementing of instruction.- Evaluating instruction.- Evaluating the curriculum.- Problems in curriculum development.- Curriculum products.
Keywords: Curriculum